Suggested excess of occupational cancers in Norwegian offshore workers: preliminary results from the Cancer Registry Offshore Cohort - Aas, Gjøril Bergva; Aagnes, Bjarte; Strand, Leif Åge; Grimsrud, Tom K. (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVE ': 'The aim of this communication was to report the overall incidence of cancer in a cohort of male Norwegian offshore oil workers. ' ' METHODS ': 'The Offshore Cohort was comprised of >25 000 men who were employed at installations in the North Sea in the period 1965–1999, and who responded to a questionnaire that included work history offshore, other occupational experience, education, leisure-time activities, and lifestyle factors. Calculating standardized incidence ratios (SIR), we compared the number of prospective incident cancers diagnosed between 1999 and 2005 with those expected for age-, gender- and period-specific rates in the general Norwegian population. ' ' RESULTS ': 'The overall cancer incidence did not differ from that of the reference population [SIR=1.0, 95% confidence interval (95% CI) 1.0–1.1, N=695]. There were indications of excess risks of acute myeloid leukemia (SIR=2.0, 95% CI 1.0–3.7) and cancer of the pleura (SIR=2.2, 95% CI 0.9–4.6). No data on occupational history was used in these preliminary analyses. ' ' CONCLUSIONS ': 'The cohort was relatively young and an extended observation period would be important for in-depth analyses. The suggested excess of leukemia and cancer of the pleura may be linked to occupational exposure during employment offshore; this issue needs to be addressed in further studies.
Keywords: cancer; cancer of the pleura; Cancer Registry Offshore Cohort; leukemia; Norway; occupational cancer; offshore worker; prospective cohort study; short communication; upstream petroleum industry